Left Atrium plactics During correction of Mitral Valve Deasease - Popov, V. V.; Spysarenko, S. P.; Malysheva, T. A.; Lazorishinetz, V. V. (Ukrainian Journal of Cardiovascular Surgery, 2018)
Objective is to determined possibillities of left atrium (LA)`s plasty (LAR) during mitral valve replacement (MVR). During 1.01.1996 – 1.01. 2018 yy.704 adult patients (pts) were operated with MVD and dilatation of LA at Institute. MVR were performed in the most pts. LAR including ligation of LA`s auriculum was performed in 522 pts (group A) and in other 182 pts only MVR (group B). All operations were performed with cardiopulmonary bypass and moderate hypothermia with crystalloid cardioplegia. There were 9 deaths at the hospital period (hospital mortality (HM) – 1,7%) (group A). Plasty of LA during isolated MVR was allowing to improve LA`s morphometry during postoperative period comparing with group B (p<0,05).